Penggunaan Media Pembelajaran IPS Berbasis Google Sites Di SMP Negeri 2 Gandrungmangu - Slamet Slamet; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2022)
The limitations of print media in terms of the amount, type and quality of data as well as the presence of technology to facilitate learning are the reasons for using Google sites-based media which are easier and more practical as well as up to date data according to the digital era or 21st century learning. The purpose of research on media use Social studies learning based on the Google site at SMP Negeri 2 Gandrungmangu is able to increase students' interest and motivation in learning and provide a learning experience that is different from conventional learning. Researchers made 1 social studies learning media based on Google Site with simple and limited development containing material from teaching material sources. The focus of the research is according to the purpose not on media development, so the method chosen is descriptive qualitative method. In collecting data using the observation method during learning practices with Google Sites media in a pandemic situation through limited face-to-face interviews, interviews were used to determine students' online learning experiences with social studies learning media based on Google Sites at home and documentation during learning. The results of this study include: increased student interest in learning media, student motivation, students' seriousness to pay attention to the material. The obstacles and problems encountered are the internet which is less stable.